Fatigue evaluation of the rib-deck weld in OSDs considering the effect of asphalt-steel interface bonding property. Issue 8 (June 2023) - Wang, Qiudong; Fu, Zhongqiu; Wei, Yang; Wang, Yixun
The interface bonding layer is usually adopted to connect the asphalt surfacing and steel deck plate; however, the effect of interface bonding conditions on fatigue performance of rib-deck welds still remains unclear. In this study, comprehensive finite element analysis was carried out to clarify the effect of interface bonding conditions. Parametric analysis was conducted to investigate the effect of Poisson's ratio and elastic modulus of asphalt surfacing, and the interface bonding condition on fatigue performance of rib-deck welds, so is the coupled effect of elastic modulus and interface bonding condition. Taking into account the time-variant temperature and traffic volume, the accumulated fatigue damages in rib-deck welds were compared and analysed. Results show that the simulation of the interface bonding condition is reliable, as convinced by bending tests. The interface bonding condition and the elastic modulus of asphalt surfacing, which are both sensitive to the temperature, considerably affect the fatigue performance of rib-deck welds. The fatigue damage of rib-deck welds is underestimated if the interface bonding behaviour is not considered.